Swelling in the Floor of the Mouth: A Diagnostic Dilemma - Datta, Ginni (Ann Maxillofac Surg, 2020)
Epidermoid cysts are abnormal structures originating from abnormal ectoderm and are benign and slow growing. These are found anywhere in the body. They arise during embryonic fusion due to entrapment of epithelial remnants and sometimes due to faulty implantation of the epithelium. The cysts can be epidermoid (squamous epithelium), true dermoid (skin apppendages), and teratoid (all germ layers). They are usually diagnosed by fine-needle cytological aspiration and require imaging to plan line of treatment. Diagnostic dilemma is always an issue as cystic lesions are commonly found in the head-and-neck region. Here, we present a case of large epidermoid cyst involving sublingual and submandibular region.